Karyomorphological Analysis of Eight Allium L. (Amaryllidaceae) Species from Turkey - Kiran, Yasar; Arikboga, Gulsah; Dogan, Gulden; Eroglu, Huseyin; Pinar, Suleyman Mesut (Univ Tokyo Cytologia, 2022)
The chromosome numbers and karyotypes of eight species of the genus Allium distributed in Turkey were analyzed. These taxa are A. armerioides Boiss., A. orientale Boiss., A. stamineum Boiss., A. tuncelianum (Kollmann) Ozhatay, B.Mathew & Siraneci, A. subakaka Razyfard & Zarre, A. muratozelii Armagan, A. duma-nii Koyuncu & Kocyigit and A. colchicifolium Boiss. Four of them (A. armerioides, A. tuncelianum, A. mura-tozelii and A. dumanii) are endemic in Turkey. The chromosome numbers of all studied taxa were determined as 2n=2x=16, while A. dumanii had the chromosome number 2n=2x=16+2B. A basic number of x=8 was confirmed for all investigated species. Haploid chromosome lengths varied from 91.48 mu m (A. armerioides) to 176.16 mu m (A. colchicifolium) among species. Karyotype analysis indicated that Allium taxa generally are sym-metrical, consisting of metacentric and submetacentric chromosome pairs. Only A. stamineum has subtelocentric chromosomes. Satellites were observed in three species; A. tuncelianum, A. subakaka, and A. armerioides. The karyotypes of A. muratozelii and A. armerioides were determined for the first time in this study.
Keywords: Amaryllidaceae; Allium; Chromosome number; Karyotype; Turkey